The Improvement of Paclitaxel Cytotoxicity using Nanocellulose based Nature Resources - R Nahrowi; A Setiawan; Noviany Noviany; Irza Sukmana; Suripto Dwi Yuwono (Journal of Engineering and Scientific Research, 2019)
Paclitaxel is one of the cancer drugs that often used. These drug kills cancer cells by inhibiting mitotic cycle. The efficiency of paclitaxel is increased by the use of nanomaterials as a carrier of paclitaxel. Nanomaterials can enhance encapsulation efficiency, improve the drug release to the target cell following nanomaterial degradation, and improve local accumulation of drug in the cellthrough endocytosis receptor. Nanomaterial that often used forencapsulation of paclitaxel is a polymer derived from natural resources such as cellulose. The advantages of cellulose as a carrier of paclitaxel are nontoxic, biodegradable, and very abundant from various sources. One of the potential sources of cellulose for drug delivery system is cassava baggase.